Growth rates in blackberry (Rubus alpinus Macfad) plants under different pruning systems (2016)
In Colombia, the blackberry is an important perennial crop for the economic sustainable development of medium and smallholder farmers. Pruning is essential for this crop and aims to renew the productive, fruit bearing branches and normalize the sink-source relationships of photoassimilates. The establishment of physiological indices and growth curves for blackberry crops with different pruning practices will develop proposals for the agricultural handling of this species. In this study, two-year-old blackberry crops were used with a T-trellis; 48 canes were grouped into three pruning treatments; a) control: without pruning; b) short pruning: canes with a 1.6 m length; and c) long pruning; canes with a 2.6 m length. The length of the canes, and the number of leaves and panicles were registered over time, in terms of days after sprouting. The curves and rates of growth were established with a functional analysis. The logistic model was ideal for expressing the growth of the plants. The maximum length of the canes was seen at 231 days after sprouting: 535 cm. The relative growth rate of the canes decreased gradually over time. The values of the absolute growth rate of the canes as well as the number of leaves and panicles decreased over time too. The maximum number of leaves was seen from 55 to 231 days after sprouting; the flowering in the plants in the pruned treatments started at 126 days after sprouting. The average number of inflorescences was 18 in the shrubs without pruning, 10 with the short pruning and 21 with the long pruning. The results showed that pruning is a determinant factor in the physiological and productive development of blackberry shrubs and that the long pruning, with a 2.6 m length, was the best pruning alternative.